(untitled) (Contemporary Mathematics, 2024)
We present some new results on the existence of fixed points for multivalued contractive type mappings involving generalized distance on metric type spaces. In support of our main results, some examples are also given. Finally, we conclude that our new presented results either improve or generalize some interesting fixed point results of the existing literature.